Exclusive Breastfeeding and Its Association with Socio-Demographic Profile of Mother in a Tertiary Care Hospital of Central India - Akulwar, Shivani Sunil; Doshi, Tejal; Saoji, Ajeet (National Journal of Community Medicine, 2018)
Introduction: Breast milk is an ideal food that serves as a complete source of infant nutrition. Exclusive breastfeeding (EBF) is defined as infant receives no other food or drink, not even water, except breast milk (including milk expressed or from a wet nurse) for 6 months of life, but allows to receive ORS, drops and medicinal syrups (vitamins, minerals and medicines). The study aimed to find out prevalence of exclusive breastfeeding and its socio demographic determinants. Methodology: Study has been conducted in the Immuno- Prophylaxis Clinic of a tertiary care hospital. All infants aged 6 months – 12 months have been included in the study. Data has been collected from mothers of infants with the help of semi structured questionnaire. Results: Early Initiation of breastfeeding was done by 55% of mothers, while 29.4% mothers gave pre-lacteal feeds. Only 59.4% of mothers exclusively breastfed their infants for first 6 months of life. The study revealed factors positively associated with EBF such as higher maternal educational level, moderate maternal age (25 - 29 yrs.), and middle socio economic status. No association was found with maternal employment and family size in this study. Conclusion: The findings from present study highlight the impor- tance of educating and counselling mothers on specifically about exclusive breastfeeding practices.